The banking business - Santos Jiménez, Néstor (2001)
The financin of an enterprise is represented with the resources used to get the necessary assets to develop its operations. One of this tools is given through the financial system, in which we can find the banks. A ban entity has its own matrix (row material-product), the resources that gets through deposists (saves accounts and others),that with its own capital are invested in viable business using differents ways. Commonly a company makes both type of business, in the first case with its cash exceeds looking for high interest and low risk; on the other hand, its cash needs are financing through debt documents- banking documents- to be added to the amounts given as capital by the shareholders.